PENGARUH JARAK TANAM DAN PACLOBUTRAZOL TERHADAP PRODUKSI DAN VIABILITAS BENIH BUNGA MATAHARI (Helianthus annuus L.) - Ramlafatma, ,; Widajati, Eny; Budiarti, Tati (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 1999)
The research was conducted at Seed Science and Technology Field Experimental and Laboratory, Faculty of Agriculture, Bogor Agricultural University since January until July 1998. Randomized Block Design was used in this experiment which consist of two factors and three I replications. The first factors were row spacing 60 cm x 25 cm (J1) and 60 cm x 45 cm (J2) and the second factors were application of 100 ml paclobutrazol/plant with concentration 0 ppm (P1), 125 ppm (P2), 250 ppm (P3) and 500 ppm (P4). The plant height was increased at narrow spacing especially at 0 ppm paclobutrazol. Paclobutrazol application reduced plant height, increased stem diameter and it's caused minimal lodging at generatif period. The highest seed production per plot was resulted at 60 cm x 25 cm with 250 ppm and 500 ppm of paclobutrazol (146 % and 155 % as compared with control treatment), and the highest seed production per plant showed at 60 cm x 45 cm and 60 cm x 25 cm with 500 ppm of paclobutrazol (197 % and 198 % compared with control treatment). Paclobutrazol125 ppm, 250 ppm, and 500 ppm increased flower diameter, number seed per flower, 1000 seed weight, germination capacity, and seed vigour. The optimum combination of treatment was showed at 60 cm x 25 cm and 250 ppm of paclobutrazol.